Results of Discectomy and Implantation of Peek Intervertebral Keys for Cervical Disk Herniation (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cervical osteochondrosis is the second most common disease after lumbar osteochondrosis and most often occurs in patients of working age 25–60 years [1]. The risk of herniated discs in the cervical spine is associated with a high probability of developing myelopathy, which leads to serious neurological disorders, decreased quality of life, and disability. The cervical segment of the spinal column is a complex anatomical and biomechanical structure. It exhibits the highest degree of mobility among all spinal segments, making it a pivotal component in the preservation of overall sagittal balance and functional integrity [2]. The curvature of the cervical segment is shaped by a range of factors, such as muscle tone distribution in the neck and shoulder girdle or the shape of the thoracic and lumbosacral segments. The curvatures of individual spinal segments influence each other. Regrettably, similar to other spine regions, the cervical segment is susceptible to degenerative alterations that may necessitate surgical intervention. The primary aim of the treatment for degenerative disc disease of the cervical spine is to decompress neural structures and pre serve the former height of the disc space and foramina. Anterior cervical discectomy without the simultaneous insertion of a graft or cage is not recommended because there is a possibility of future instability and kyphotic malalignment of the cervical spine [3]. Anterior cervical discectomy and fusion (ACDF) is currently the gold stan dard for surgical treatment of degenerative disc disease of the cervical spine. An interbody implant should have a size that produces a tight interference fit and maximizes the dimensions of the graft–vertebral body interface. Popular methods include an ACDF using a standalone cage or a cage with a cervical plate. However, it is still debatable whether a plate is necessary for enhanced treatment ment outcomes [4]. Both methods have their advantages and disadvantages. Most surgeons believe that plating is not necessary for single-level surgery, but operations on multiple levels require additional strengthening of the fixation obtained using a cervical plate. This paper reviews current literature reports, with insight added from the au thors' experience. Anterior cervical plates may increase interbody fusion rates and stability, maintain or improve cervical sagittal alignment, and prevent subsidence, particularly in multiple-level ACDFs [5]. However, anterior plating may also be associated with potential disadvantages and complications. The complications associated with plate fixation consist of esophageal soft tissue damage, neurovascular injuries and dysphagia. The success of surgery for cervical disc disease depends fundamentally on the appropriate decompression of neural structures.This is the main determinant of postoperative clinical improvement measured using scales which show changes in pain intensity and quality of life [6].